EKSISTENSI DAN PERAN ALUMNI DALAM MENJAGA KUALITAS MUTU JURUSAN AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS MATARAM - Anggun Hilendria; L. Takdir Jumaidi; Lukman Effendi; Widya Astuti (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2019)
Graduates are a product description of a factory in this case that is correlated with educational institutions. A quality factory will produce quality products, and vice versa. However, if the factory is only concerned with quantity, then it can be ascertained that the percentage of quality is numbered, as a result the product is not as expected. Graduates as the final product produced by higher education has an important role for the quality and existence of the universities that have graduated it. Therefore, strategic efforts in order to pay attention to the existence of graduates must be done, because in addition to being a quality target of a college, graduates are also a medium of evaluation and a benchmark for the success of a college. The benefits of graduates for tertiary institutions are very large for the long-term sustainability of various processes. Graduates have a very strategic role in their work to devote knowledge and work in the community. Based on this, the Accounting Department of Economic and Bisnis Faculty considers that it is necessary to do a tracer study periodically (every year) to monitor them so that the existence and role of graduates can maintain the quality quality of the Accounting Department of Economic and Business Faculty Mataram University. Based on the results of the study, it can be concluded that the Accounting Department of Economic and Business Faculty Mataram University should not ignore the existence of its graduates, because it is also related to stakeholders who will provide assessment, which will also influence the existence and development of the relevant institutions in the view of the community as stakeholders. Accounting Department of Economic and Business Faculty Mataram University is deemed necessary to provide internship courses or field work practices to students so that they know the conditions of the world of work and improve the English language skills of students to be able to compete in the world of work. In addition, the Accounting Department of Economic and Business Faculty Mataram University continuously carried out tracer studies and reported them as a form of institutional commitment to improve the quality of the institution's quality.